The effect of Aluminium chloride injection in arcuate nucleus on sperm count and the weight of vas deferens and epididymis in rat - M.R SHaraki; S Zahediasl; A.R Sarkaki (Journal of Kerman University of Medical Sciences, 2000)
Aluminium is a blocker of voltage sensitive cakcium channels which intere the body from different soueces.this ion interferes with biological function of Ca++ion.because GnRH synthesis,secretion and spermatogenesis on vas deferens and epididymis sperm count and weight of these organs in male rats.the study was performed on four group of rats(n=49),in whom the arcuate nuleus was bilateraly cannulated by sterotaxic surgery.test group recieved 100 nl ACSF containing 0.15 pmol aluminiym in each side of the arcuate nucleus for 20 days.two groups of animals were recieve the same volume of ACSF with PH=7.2 and 3.4. the sham control group did not recieve any agent after cannulation.at the end of experiment ,animals were anethetised with nesdonal(sodium thiopental) and then vas deferens and epididymis were removed and weighted.these organs were cut and diluted with normal saline.sperms were counted by chmocytometer and calculated per gram of tissuse.results showed that sperm count per gram of tissue in vas deferens and epididymis control group were 107.9+_2.5,76.2+_16.3 million and in test group 45.0+_2.9,67.3+_4.9 million respectively (p<0.05).the weight of these organs in AICI3 group were 103.5+_5.01,462.3+_19.2 mg,and in control group were 117.5+_2.5,515+_16.3 mg respectively.the value of testosterone in control and test groups were 2.11+_0.4,0.8+_0.28 ng/ml (p<0.05).overall the results indicate that injection of aluminium in male rat arcuate nucleus,can decrease sperm count in vas deferens and epididymis.in addition the weight of this organs and serum testosterone were also decreased.